Implementasi Teknologi Hidroponik Metode Nutrient Film Technique dengan Sistem Monitoring Internet of Things untuk Pemberdayaan Masyarakat Desa Kaligung Banyuwangi - Holik, Abdul; Khirzin, Muhammad Habbib; Laksanawati, Trias Ayu (Universitas Nusantara PGRI Kediri, 2024)
Kaligung Village, Banyuwangi, faces challenges in increasing agricultural productivity owing to limited land and access to modern technology. To address these problems, community service activities aim to introduce and implement Nutrient Film Technique (NFT) hydroponic technology integrated with the Internet of Things (IoT) system. This activity begins with socialization, which aims to increase the understanding of the village community regarding hydroponic technology and IoT systems. The next stage involved practical demonstrations to train villagers in the processes of seed preparation, nutrient mixing, and real-time monitoring of plant conditions through IoT technology. In the final stage, intensive mentoring was conducted to provide guidance and solutions to technical problems, particularly in measuring and mixing nutrients. The evaluation results showed that the program succeeded in improving the skills and understanding of the village community by utilizing modern hydroponic technology. Through a combination of socialization, practical training, and mentoring, villagers can efficiently implement and manage the NFT hydroponic system, including monitoring plant growth through the IoT system. It is hoped that the application of this technology can significantly increase agricultural productivity in Kaligung Village and become a solution to the challenges of limited land and access to technology faced by the region.